Recurrent cavernous orbitocranial hemangioma. A clinical case and a literature review - N. K. Serova; A. P. Trunova; N. N. Grigoreva; V. A. Cherkaev; V. V. Nazarov (Российский офтальмологический журнал, 2022)
Cavernous hemangioma of the orbit (CHO) is a vascular space-occupying lesion that develops as a result of an abnormal anlage of the vascular system and occurs in 70% of patients with vascular neoplasms of the orbit. CHO is more often considered as a venous malformation with slow blood flow, rather than a benign tumor. Very rarely CHO spreads into the cranial cavity, usually through the upper orbital fissure and the optic canal. The recurrence of CHO after its complete removal is low, however no reliable data are available. It is supposed that CHO relapse can occur in three cases: the continued growth of an incompletely removed tumor, growth of an undiagnosed space-occupying formation, and the emergence of a new tumor. The purpose of the study is to present a clinical case of a multiple recurrence of orbitocranial cavernous hemangioma. The clinical case demonstrates such a recurrence after an incomplete CHO removal, which was manifested by exophthalmos and moderate oculomotor disorders. Special features of the clinical case also include CHO spread into the cranial cavity accompanied by a cavernous hemangioma of the brain structure.